Article RETRACTED due to manipulation by the authors Biomechanical Analyses of Scoop in Field Hockey - Ahmad Chaeroni; Ikram Husain; Mottakin Ahmed; Agam Pratap Singh; Md Abu Sayed; Ardo Okilanda; Nurul Ihsan; Padli Padli; Hengki Kumbara; Jeki Haryanto; Mario Febrian (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Field hockey is an Olympic sport played all over the world. Hockey is played with a stick where one requires endurance, agility, balance coordination, and high skill to convert the shot. There are various kinds of skills i.e. hitting, dribbling, scooping, tackling etc. Only scoop was selected for the study in different phases (stance phase, execution phase, follow through phase). Field hockey scoop is the aerial passing by lifting the ball from the ground inserting head of hockey stick under the ball. Scoop plays vital role in competitive field hockey games.  The aim of the study was to find out the kinematic difference in the elbow joint, knee joint, and ankle joint. The objective of the study was to find out the angular differences of elbow joint, knee joint, and ankle joint in different phases of delivery of field hockey scoop shot. Researchers hypothesised that there are significance differences in elbow joint angle, knee joint angle, and ankle joint angle during delivering of field hockey scoop shot. Six males inter university players aged from 20-24 years were selected for the study and at least they represented at inter university games /national level. Set of the camera is at 1.10 m in height and 3.70 meters. The focal length is 5.6, the resolution is 1080, and the frame rate is 100 per sec. A Sony FRD-AX700 camera was placed 3.7 meters apart on the right side of the hockey player. Angle of elbow joint, angle of knee joint, angle ankle joint, cadence, stride length, and numbers of frames were analysed using Kinovea 0.9.5 software. This research will help the players to execute scoop after knowing elbow joint angle, knee joint angle, and ankle joint angle.